Front Cover: Synthesis and Reactivity of Tris(pentafluoroethyl)gallium Compounds (Eur. J. Inorg. Chem. 30/2019). Issue 30 (8th August 2019) - Niemann, Mark; Neumann, Beate; Stammler, Hans‐Georg; Hoge, Berthold
Abstract : The Front Cover shows a Gallic village besieged by Roman legions. Against these "cationic" legions, the village is protected by the weakly coordinating anion [Ga(C2 F5 )4 ] –, obtained from a magic potion. The ingredients consist of the fundamental material LiC2 F5 and the gallium extracts [Ga(C2 F5 )3 (OEt2 )], [Ga(C2 F5 )3 (dmap)], or the "fresh fish" [Ga(C2 F5 )3 F] – . The element gallium is additionally symbolized by a gallium anvil and the rooster (Latin "gallus") in the background. The stability of the pentafluoroethylgallium compounds towards water is shown by the ocean in the background. A big thanks goes to Dr. Julia Bader for drawing the cover picture. More information can be found in theFull Paper by B. Hoge et al. For more on the story behind the cover research, see theCover Profile .